2008
DOI: 10.1016/s0828-282x(08)70629-9
|View full text |Cite
|
Sign up to set email alerts
|

The D-dimer assay: A possible tool in the evaluation of atrial thrombosis

Abstract: A trial fibrillation (AF) is the most common sustained arrhythmia seen in clinical practice, and affects more than 4% of the population older than 60 years of age (1,2). Peripheral thromboembolism and ischemic stroke contribute significantly to the observed mortality and morbidity rates. AF contributes to 15% to 20% of all strokes (1,3), and emboli arise predominantly from the left atrial appendage (LAA) (4). Hence, there is a need to exclude atrial thrombi before cardioversion in symptomatic AF. A recent larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Over the last 2 decades, numerous studies have explored the predictive value of D-dimer levels in thromboembolic and cardiovascular events with AF. [ 2 , 27 29 ] Some studies [ 30 , 31 ] found that D-dimer can be used as a possible test to exclude left atrial thrombus. Transesophageal echocardiography (TEE) is the gold standard for left atrial thrombus.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last 2 decades, numerous studies have explored the predictive value of D-dimer levels in thromboembolic and cardiovascular events with AF. [ 2 , 27 29 ] Some studies [ 30 , 31 ] found that D-dimer can be used as a possible test to exclude left atrial thrombus. Transesophageal echocardiography (TEE) is the gold standard for left atrial thrombus.…”
Section: Discussionmentioning
confidence: 99%
“…The D‐dimer levels decreased significantly within 2 days after MO exchange. The slow decrease is explained by the half‐life of the D‐dimers of approximately 48 h . In time, exchange of the MO reduced risks of system‐induced coagulation disorder such as bleeding diathesis.…”
Section: Discussionmentioning
confidence: 99%
“…Habara et al 16 measured D-dimer level in 925 patients with nonvalvular atrial fibrillation undergoing TEE, which detected 83 LAA thrombus and yielded a negative predictive value of 97% for identifying LAA thrombus for a cut-off value of D-dimer. D-dimer levels have been shown to be increased in AF especially in patients having multiple risk factors for embolism in earlier studies 17,18 . Ibebuogu et al 18 described a case where elevated D-dimer resulted in performance of TEE, which documented atrial thrombus in a patient with infective endocarditis, atrial fibrillation and pulmonary edema and saved the patient from complications of cardioversion, which should have resulted from emergency cardioversion.…”
Section: Discussionmentioning
confidence: 92%